Regge models of proton diffractive dissociation based on factorisation and structure functions - Jenkovszky, László; Schicker, Rainer; Szanyi, István (Entropy, 2022)
Recent results by the authors on proton diffractive dissociation (single, double and central) in the low-mass resonance region with emphasis on the LHC kinematics are reviewed and updated. Based on the previous ideas that the contribution of the inelastic proton-Pomeron vertex can be described by the proton structure function, the contribution of the inelastic Pomeron-Pomeron vertex appearing in central diffraction is now described by a Pomeron structure function.
Gesehen am 06.09.2022